A global review of marine air pollution policies, their scope and effectiveness. (15th October 2021) - Gössling, Stefan; Meyer-Habighorst, Christiane; Humpe, Andreas
Abstract: Shipping is associated with various environmental impacts, such as pollutants discharged to air and sea. Much of this pollution appears to be unregulated, and global emissions from shipping are expected to more than triple between 2020 and 2050. This paper reviews global, national, regional and port-level legislative approaches that have been implemented to reduce emissions of carbon dioxide (CO2 ), nitrous oxides (NOx ), sulphur oxides (SOx ) and particulate matter (PM). Policies are identified on the basis of a systematic review of the literature in combination with a detailed analysis of the respective global, national and local policy initiatives. Findings suggest that many policies are voluntary or, in ports, incentive-based; regulatory approaches are largely limited to Emission Control Areas. Policies also focus on efficiencies, they are not concerned with absolute pollutant and greenhouse gas levels. No policies incentivizing or forcing the transition to zero-carbon fuels were identified. As ports can define limits to pollution, for instance by demanding shore power use, they can significantly affect the clean development of the sector. Further legislation will be needed nationally to counterbalance the lack of supranational ambition on pollutants and climate change mitigation. Graphical abstract: Image 1 Highlights: Reviewed global marine policies targeting air pollutants (CO2, NOx, SOx, PM). The number of global, national and port level policies is limited. Current policies are focused on relative improvements, not overall emissions caps. Current policies are unlikely to sufficiently achieve pollutant reduction goals.